The Routledge handbook of global historical archaeology
1 online resource
Keywords: "The Routledge Handbook of Global Historical Archaeology is a multi-authored compendium of articles on specific topics of interest to today's historical archaeologists, offering perspectives on the current state of research and collectively outlining future directions for the field. The broad range of topics covered in this volume allows for specificity within individual chapters, while building to a cumulative overview of the field of historical archaeology as it stands, and where it could go next. Archaeological research is discussed in the context of current sociological concerns, different approaches and techniques are assessed, and potential advances are posited. This is a comprehensive treatment of the sub-discipline, engaging key contemporary debates, and providing a series of specially-commissioned geographical overviews to complement the more theoretical explorations. This book is designed to offer a starting point for students who may wish to pursue particular topics in more depth, as well as for non-archaeologists who have an interest in historical archaeology. Archaeologists, historians, preservationists, and all scholars interested in the role historical archaeology plays in illuminating daily life during the past five centuries will find this volume engaging and enlightening"--